Konsep Siyasah dalam Yahudi dan Islam - Anshori, Ahmad Yani (UIN Sunan Kalijaga, 2016)
The essence of siyasah is the management of the umat`s affairs by the government based on akhlak. Siyasah held in certain territory and particular political contract anyway. The aim is to establish the religion and maintain worldly affairs towards the common maslahah. In the discourse of history, the responses to siyasah are different. There are who regard siyasah as the cause of Muslim`s stagnation, but the others assert siyasah as the foundation, pillar, and moral to regulate state and government. The discourse of siyasah in Jews and Islam are the real examples of these responses.